The Security Council’s Non-Determination of a Threat to the Peace as a Breach of International Law - Đipalo, Sabina (Pécs journal of international and European law, 2018)
This paper is focused on characterizing the inaction of the Security Council as a failure in the enforcement of international law in the field of collective security. Moreover, such lack is also believed to be a breach of the rule of international law which is to lead to responsibility of the United Nations as an international organisation. Security Council’s omission in determining the situation in Iraq in 2014 a threat to international peace and security is seen as contrary to the primary rule of Article 39 of the Charter of the United Nations, which sets an obligation, not merely a possibility or a privilege realisable within a wide margin of discretion. Examples of its past actions in comparable situations are given in order to demonstrate the developed practice that has become established practice of determining threats to the peace in cases of humanitarian crises. A short overview of the General Assembly’s and the Secretary-General’s (in)activities is given as well.